Patient evaluation of the use of follitropin alfa in a prefilled ready-to-use injection pen in assisted reproductive technology: an observational study - Welcker, J Thomas (BioMed Central, 2010)
BACKGROUND: Self-administration of recombinant human follicle-stimulating hormone (r-hFSH) can be performed using injection pen devices by women undergoing assisted reproductive technology procedures. The objective of this study was to explore the use of the prefilled follitropin alfa pen in routine assisted reproductive technology procedures in Germany. METHODS: This prospective, observational study was conducted across 43 German IVF centres over a period of 1.75 years. Patients who had used the prefilled follitropin alfa pen in the current or a previous cycle of controlled ovarian stimulation completed a questionnaire to assess their opinions of the device. RESULTS: A total of 5328 patients were included in the study. Of these, 2888 reported that they had previous experience of daily FSH injections. Significantly more patients reported that less training was required to use the prefilled follitropin alfa pen than a syringe and lyophilized powder (1997/3081 [64.8%]; p < 0.001 'less' versus 'more' training). Significantly more patients rated the prefilled follitropin alfa pen as easier in terms of use (2321/3206, 72.4%; p < 0.001 'much more easy' versus 'less easy') and daily injection (2384/3262, 73.1%; p < 0.001 'much more easy' versus 'less easy') than existing injection methods. Approximately one third of respondents rated the prefilled follitropin alfa pen as easier to use than the follitropin beta pen with reloadable cartridges. The majority (3378/4024, 83.9%) of patients had a general preference for the prefilled follitropin alfa pen over other injection methods. CONCLUSIONS: In this questionnaire-based survey, routine use of the prefilled follitropin alfa pen was well accepted and associated with favourable patient perceptions. Users of the pen found it easier to initially learn how to use, and subsequently use, than other injection methods. In general, the prefilled follitropin alfa pen was the preferred method for self-administration of gonadotrophins. Together with previous findings, the results here indicate a high level of patient satisfaction among users of the prefilled follitropin alfa pen for daily self-administration of r-hFSH.